2009
DOI: 10.1029/2008wr007470
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall redistribution in a tropical forest: Spatial and temporal patterns

Abstract: [1] The investigation of throughfall patterns has received considerable interest over the last decades. And yet, the geographical bias of pertinent previous studies and their methodologies and approaches to data analysis cast a doubt on the general validity of claims regarding spatial and temporal patterns of throughfall. We employed 220 collectors in a 1-ha plot of semideciduous tropical rain forest in Panama and sampled throughfall during a period of 14 months. Our analysis of spatial patterns is based on 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
92
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 60 publications
12
92
1
3
Order By: Relevance
“…First, due to the decreasing coefficient of variation with increasing event size (Fig. 5a) (Brauman et al, 2010;Carlyle-Moses et al, 2004;Holwerda et al, 2006;Loustau et al, 1992;Price and Carlyle-Moses, 2003;Staelens et al, 2006;Vrugt et al, 2003;Zhang et al, 2006;Zimmermann et al, 2009), the sampling effort necessary to reach a pre-specified error limit of mean throughfall estimates decreases alike (Kimmins, 1973;Price and Carlyle-Moses, 2003;Rodrigo and Àvila, 2001;Zimmermann et al, 2010). The results of our study are in line with these findings (Figs.…”
Section: Implementing Throughfall Sampling Schemes: Influence Of the supporting
confidence: 82%
See 4 more Smart Citations
“…First, due to the decreasing coefficient of variation with increasing event size (Fig. 5a) (Brauman et al, 2010;Carlyle-Moses et al, 2004;Holwerda et al, 2006;Loustau et al, 1992;Price and Carlyle-Moses, 2003;Staelens et al, 2006;Vrugt et al, 2003;Zhang et al, 2006;Zimmermann et al, 2009), the sampling effort necessary to reach a pre-specified error limit of mean throughfall estimates decreases alike (Kimmins, 1973;Price and Carlyle-Moses, 2003;Rodrigo and Àvila, 2001;Zimmermann et al, 2010). The results of our study are in line with these findings (Figs.…”
Section: Implementing Throughfall Sampling Schemes: Influence Of the supporting
confidence: 82%
“…5c and d). The detected decrease of correlation lengths with increasing event size confirms results of previous studies which indicated a particularly pronounced influence of the canopy structure on throughfall patterns for small events (Carlyle-Moses et al, 2004;Loustau et al, 1992;Zimmermann et al, 2009). The consequence in terms of sampling is the poor performance of troughs when low nugget-to-sill ratios coincide with effective ranges that exceed a couple of meters (Fig.…”
Section: Implementing Throughfall Sampling Schemes: Influence Of the supporting
confidence: 77%
See 3 more Smart Citations